Dependence structure, relational mechanisms and performance: teasing out the differences between upstream and downstream supply chain partners - Pu, Xiaodie; Cai, Zhao; Chong, Alain Yee Loong; Paulraj, Antony (International journal of operations & production management, 2023)
PurposeFirms are subject to power from both upstream and downstream partners; those partners may have different or even opposing impacts on supply chain relationships and financial performance. The purpose of this study is to investigate how upstream and downstream dependence structures affect a firm's financial performance through upstream and downstream relational depth (DEP) and relationship extendedness (EXT).Design/methodology/approachData representing both upstream and downstream supply chain perspectives was collected using a multiple-respondent survey and was further augmented using financial performance data from an archival database.FindingsDependence advantages (ADVs) and disadvantages from upstream and downstream partners affect relational mechanisms and firm performance differently. Only downstream ADV will enhance a firm's DEP and EXT and subsequently affect firm's revenue and profit. Contradictory to widely held belief, the results reveal that firms that maintain long-term relationships with buyers and suppliers may experience lower revenue/profit.Originality/valueThis research represents a significant step in understanding the economic ramifications of dependence by (1) highlighting the difference between upstream and downstream supply chain dependence structure and (2) understanding the indirect effects of dependence structure on financial performance.